2007
DOI: 10.1902/jop.2007.060358
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis Is Associated With Aggravation of Prediabetes in Zucker Fatty Rats

Abstract: Prediabetes worsened periodontitis, and periodontitis, in turn, was associated with deterioration of glucose metabolism in ZFRs, suggesting a progress toward diabetes. Furthermore, periodontitis also affected glucose regulation in lean rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…The metabolic syndromes associated with increased level of FFA, diabetes, and atherosclerosis have been demonstrated to be highly related to bone loss ( 9, 13 ). More alveolar bone loss is associated with the Goto-Kakizaki rat, a type 2 diabetes rat ( 22 ), and the Zucker fatty rat, a known model of prediabetes ( 23 ). Lower BMD and rapid bone loss is associated with the advanced aortic calcifi cation, a surrogate marker for atherosclerosis, in postmenopausal women ( 24 ), and a graded association is also found between atherosclerotic vascular calcifi cation and vertebral bone loss ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic syndromes associated with increased level of FFA, diabetes, and atherosclerosis have been demonstrated to be highly related to bone loss ( 9, 13 ). More alveolar bone loss is associated with the Goto-Kakizaki rat, a type 2 diabetes rat ( 22 ), and the Zucker fatty rat, a known model of prediabetes ( 23 ). Lower BMD and rapid bone loss is associated with the advanced aortic calcifi cation, a surrogate marker for atherosclerosis, in postmenopausal women ( 24 ), and a graded association is also found between atherosclerotic vascular calcifi cation and vertebral bone loss ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…the effect of periodontitis on the diabetic condition are also emerging using animal model systems. For example, induction of periodontitis in prediabetic rats causes impaired glucose tolerance 51, 52 . In addition, induction of periodontitis accelerates the development of insulin resistance and the onset of T2DM in animals fed a high fat diet 48 .…”
Section: Possible Mechanisms Underlying These Two Way Relationshipsmentioning
confidence: 99%
“…An explanation in this regard may be derived from the fact that periodontal disease elevates the systemic burden of infl ammatory mediators (such as CRP) that aggravate the existing metabolic disorder in patients with chronic hyperglycemia [9,10], however, SRP reduces the severity of periodontal infection and decreases the systemic burden of infl ammatory mediators which in turn reduces the hyperglycemic state in prediabetic patients. An interesting fi nding in the present study was that despite reduction in the severity of periodontal infl ammation in both groups compared to baseline values, FBG levels in both groups remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies [4,[6][7][8] have shown that prediabetic patients (patients with impaired glucose tolerance) are also susceptible to periodontal destruction as compared to their systemically healthy controls. It has been proposed that local periodontal infection increases the systemic burden of infl ammatory mediators (such as C-reactive protein [CRP]), which in turn aggravate the existing metabolic disorder in hyperglycemic patients [9,10]. Additionally, increased production and accumulation of advanced glycation endproducts in periodontal tissues raised cellular oxidative stress and production and accumulation of proinfl ammatory cytokines (such as interleukin (IL)-6, IL-1β, IL-18, matrix metalloproteinase [MMP]-8, and MMP-9) in the serum, saliva, and gingival crevicular fl uid of patients with persistent hyperglycemia tend to worsen periodontal infl ammation [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%